Hubungan Antara Working Memory dengan Reading Comprehension pada Siswa Kelas 4 di SDIT Cahaya Hati Pedan Kabupaten Klaten - Ika Ayu Pratiwi, Devani; Soesyasmoro, R. Asto (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Working Memory is a memory system capable of analyzing information after receiving it and can then be displayed again (Nadira et al., 2023). Meanwhile, reading comprehension is a reading activity that involves cognitive roles in thinking, analyzing, and understanding a text (Tahmidaten & Krismanto, 2020). Thus, the ability of working memory is a cognitive component that can be related to reading comprehension ability, which requires cognitive roles in thinking. Objective: This study aims to determine the relationship between working memory and reading comprehension in fourth-grade students at SDIT Cahaya Hati Pedan, Klaten Regency. Methods: This research employs a quantitative approach with a correlational research design and a cross-sectional data collection approach. The sampling technique was carried out using simple random sampling technique. Simple Random Sampling is a sampling of part of the population where each member has the same opportunity to be selected. This study used a sample of 55 4th grade students at SDIT Cahaya Hati Pedan, Klaten Regency. The collected data will be analyzed descriptively and bivariately. The statistical test used is Spearman Rank due to the non-normal distribution of the data (non-parametric). Research Results: The results of the statistical test, specifically the Spearman rank test, indicate that the abilities of working memory and reading comprehension have a significance of 0.000 (ρ value), where 0.000 < 0.05. Therefore, Ho (null hypothesis) is rejected, and Ha (alternative hypothesis) is accepted. The strength of the relationship can be seen from the results of r = 0.589 these results indicate that the strength of the correlation is moderate and shows a positive correlation direction. Conclusion: This research concludes that there is a relationship between working memory and reading comprehension in fourth-grade students at SDIT Cahaya Hati Pedan, Klaten Regency. Keywords: Working Memory, Reading Comprehension, Grade 4 Students